Entrepreneurship for zero waste strategy in Omsk city - Kostarev, Sergey (Univerzita Pardubice, 2007)
This article deals with "zero waste" strategy for Omsk city. Developing of markets for waste recycles and services improving had been identified as priority policies and should be realized by involving wide range of small and medium enterprises. The author of this article introduces the vision of "zero waste" strategy, its background information, recyclable waste collection and segregation, waste management analysis, strategy policies, priorities and implementation plan, evaluation and developing the strategy.
Keywords: Sustainable Development; Strategy; waste management